Management and prevalence of long‐term conditions in primary health care for adults with intellectual disabilities compared with the general population: A population‐based cohort study - Cooper, Sally‐Ann; Hughes‐McCormack, Laura; Greenlaw, Nicola; McConnachie, Alex; Allan, Linda; Baltzer, Marion; McArthur, Laura; Henderson, Angela; Melville, Craig; McSkimming, Paula; Morrison, Jill (Journal of applied research in intellectual disabilities, 2018)
Background In the UK, general practitioners/family physicians receive pay for performance on management of long‐term conditions, according to best‐practice indicators. Method Management of long‐term conditions was compared between 721 adults with intellectual disabilities and the general population (n = 764,672). Prevalence of long‐term conditions was determined, and associated factors were investigated via logistic regression analyses. Results Adults with intellectual disabilities received significantly poorer management of all long‐term conditions on 38/57 (66.7%) indicators. Achievement was high (75.1%–100%) for only 19.6% of adults with intellectual disabilities, compared with 76.8% of the general population. Adults with intellectual disabilities had higher rates of epilepsy, psychosis, hypothyroidism, asthma, diabetes and heart failure. There were no clear associations with neighbourhood deprivation. Conclusions Adults with intellectual disabilities receive poorer care, despite conditions being more prevalent. The imperative now is to find practical, implementable means of supporting the challenges that general practices face in delivering equitable care.